The Anticancer Activity of Curcumin: A Literature Review - Pratia Mega Sari (HM Publisher, 2021)
Cancer is the world's second largest cause of mortality and one of the most serious public health issues. Despite significant advancements in cancer treatment, cancer incidence and mortality rates remain high. Current research is still focused on developing more effective and less hazardous cancer treatment options. Curcumin has gotten a lot of press in the last two decades as an anti-oxidant, anti-inflammatory and cancer-fighting agent Curcumin modulated intracellular signaling pathways that affect tumor growth, angiogenesis, metastasis, inflammation, invasion, and apoptosis, among other things. Curcumin suppresses tumor cell growth and enhances apoptosis via upregulating the expression and activity of p53. Curcumin also has a strong inhibitory impact on the NFB and COX2 activity, which are involved in the upregulation of antiapoptotic genes like Bcl2. It can also reduce the control of antiapoptosis PI3K signaling and enhance MAPK expression, resulting in endogenous reactive oxygen species generation. The goal of this research is to review curcumin's anticancer properties.